Effect of Customer Service Modernization on Customer Satisfaction in Shell Petrol Stations in Oman - AL BALUSHI, TALAL (2023)
Customer service modernization is a critical success factor for energy service sector companies. Influencing positive customer experience is essential for enterprises operating in this area since energy sector depends on high quality customer service delivery to influence competitive market advantage. The study determines the effect of customer service modernization on customer satisfaction in Shell petrol stations in Oman to examine the effect of service visibility, service reliability, service effectiveness and efficiency, and service customization on customer satisfaction. The research adopted a descriptive research design and a population of customers who fuel at Shell petrol stations in Oman. A sample comprising 196 customers were recruited using simple random sampling. Online semi-structured questionnaires were used to collect the primary data. Multiple regression and correlation tests were inferential statistics reported. The results reveal service visibility positively and significantly affects customer satisfaction (β1 = 0.40; p < 0.05). Service reliability positively and significantly affects customer satisfaction (β2 = 0.267; p < 0.05). Service effectiveness and efficiency positively and significantly affects customer satisfaction (β3 = 0.169; p < 0.05). Service customization positively and significantly affects customer satisfaction (β4 = 0.124; p < 0.05). Shell stations to promote customer satisfaction through quality service delivery.